2018
DOI: 10.1051/epjconf/201818504012
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of purified amorphous carbon

Abstract: In this work, magnetic properties of activated carbon coal, which is also named amorphous carbon, were investigated. Composition and structure analysis was performed by XRD, SEM and EDS techniques. Position and width of peaks on XRD pattern confirmed amorphous structure of coals with small degree of graphitization. Magnetic measurements were performed by SQUID magnetometer. According to thermomagnetic measurements, in part of the samples, antiferromagnetic transition was observed near 120 K. Nature of such phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Thus, we suggest that the origin of the ferromagnetism be attributed to the mixture of carbon atoms with sp 2 and sp 3 bonds according to the above XPS and Raman analysis, and this creates vacancies in the presence of unpaired electron spins in sp 3 carbon bonds that contribute the ferromagnetism [7,63]. In addition, the FE-SEM showed the smallest average diameter of nanofibers were possible magnetically ordered due to the large amount of graphitized carbons edge sites magnetism [18,64]. The observed ferromagnetism could be based on the rich carbon defects of carbon dangling bonds and strong ferromagnetic coupling between them [3].…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, we suggest that the origin of the ferromagnetism be attributed to the mixture of carbon atoms with sp 2 and sp 3 bonds according to the above XPS and Raman analysis, and this creates vacancies in the presence of unpaired electron spins in sp 3 carbon bonds that contribute the ferromagnetism [7,63]. In addition, the FE-SEM showed the smallest average diameter of nanofibers were possible magnetically ordered due to the large amount of graphitized carbons edge sites magnetism [18,64]. The observed ferromagnetism could be based on the rich carbon defects of carbon dangling bonds and strong ferromagnetic coupling between them [3].…”
Section: Resultsmentioning
confidence: 76%
“…Ferromagnetism in carbon exhibiting spontaneous magnetization at room-temperature was reported as early as 1987 [5]. There have been a number of publications in which reproducible observations of room-temperature magnetic ordering in different carbon allotropes, such as graphite [6][7][8][9], graphene [10], proton-irradiated highly oriented pyrolytic graphite (HOPG) [6,[11][12], carbon nanotubes [13][14][15], polymerized fullerenes [16], carbon nanofoam [17] and amorphous carbon [18] were reported. In addition, Ma et al [19] suggested the observation of room temperature ferromagnetism in a polymer which includes Teflon tape subjected to simple mechanical stretching, heating, or cutting.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 shows the XRD pattern of all samples used for investigation of their crystal structures. For all samples, diffraction peaks corresponding to the (002) and ( 101) peaks of graphitic carbon were observed at approximately 2θ = 25° and 44° [20]. The broad diffraction peaks suggest the disorder and amorphous characteristics of the materials [32].…”
Section: Resultsmentioning
confidence: 93%
“…Furthermore, the carbon atoms neighboring to defects in samples will adjust their bonds to accommodate the defects and produce dangling sp 2 bonds, which generates a magnetic moment. Thus, the origin of the ≡ ferromagnetism was suggested to be attributed to the mixture of carbon atoms with sp 2 and sp 3 bonds according to the above XPS and Raman analysis, and this creates vacancies in the presence of unpaired electron spins in sp 3 carbon bonds that contributed the ferromagnetism [10,54], In addition, the FE-SEM shows the smallest average diameter of nano bers were possible magnetically ordered due to the large amount of graphitized carbons edge sites magnetism [20,55]. The observed ferromagnetism could be based on the rich carbon defects of carbon dangling bonds and strong ferromagnetic coupling between them [3].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation